Bird diversity and mangrove forest as potential ecotourism destinations in Kapo-kapo Bay, Cubadak Island, West Sumatra, Indonesia - WILSON NOVARINO; ERIZAL MUKHTAR; AYU SMARNIA PUTRI; PUTRI LISYA ANGGRAINI (Society for Indonesian Biodiversity, 2023)
Abstract. Novarino W, Mukhtar E, Putri AS, Anggraini PL. 2023. Bird diversity and mangrove forest as potential ecotourism destinations in Kapo-kapo Bay, Cubadak Island, West Sumatra, Indonesia. Biodiversitas 24: 3583-3591. Mangrove forests play an important role in the management of the coastal ecosystem of Indonesia. Research on bird diversity has been carried out to support ecotourism attractions in the mangrove area of Kapo-kapo Bay, West Sumatra. The objective of this study is to determine the bird diversity and mangrove plant diversity in the mangrove kapo-kapo Bay area, West Sumatra, using the point count method and transect method. Mangrove plants have been found in three families, five genera, and six species. The vegetation composition on this research site is lower than that on Sumatra's east coast. The composition of mangrove trees and tree diversity was lower on the west coast of Sumatra than on the east coast. The composition and diversity of birds at the study sites were not significantly different between the mangrove forests on Sumatra's west and east coasts. Rhizophora apiculata Blume species dominate the mangrove forests in Kapo-kapo Bay, while Collocalia esculenta species dominate the birds. The analysis of the suitability of mangrove ecotourism in Kapo-kapo Bay obtained a score of 111 or 92.5%, placing it in the Very Suitable category (S1) to be developed as an ecotourism area. The presence of birds and bird habitat use in mangroves are all interesting ecotourism attractions.